2019
DOI: 10.3390/bs10010002
|View full text |Cite
|
Sign up to set email alerts
|

Russian Students’ Social Representations of Higher Education

Abstract: The ideas of the theory social representations proposed by Moscovici and developed in the structural approach by Abric were used in the research in order to reveal the structure and content of students’ social representations of higher education in a modern society. The total sample size was 572 students: of which 197 were secondary school students (average age of 16.7), 189 were undergraduate students (average age of 20.8) and 186 were master students (average age of 29.3). The methodology of Vergès for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Moreover, these studies are often very superficial due to the respondents' furtiveness and tendency to hide their true motives and feelings even without the pressure of language barrier (Sachkova & Esina, 2020). Furthermore, different psychological studies revealed the fact that communication contains only 20% of verbal information.…”
Section: Problem Statementmentioning
confidence: 99%
“…Moreover, these studies are often very superficial due to the respondents' furtiveness and tendency to hide their true motives and feelings even without the pressure of language barrier (Sachkova & Esina, 2020). Furthermore, different psychological studies revealed the fact that communication contains only 20% of verbal information.…”
Section: Problem Statementmentioning
confidence: 99%
“…Por ser uma técnica projetiva possibilita a/ao pesquisadora(dor) estruturar as respostas apresentadas a partir de um termo e/ou expressão indutor(a), em situações de evocação espontânea e imediata, bem como a identificação dos possíveis universos semânticos e consensuais de um determinado grupo, relacionados a um respectivo estímulo (11) . O uso dessa técnica tem sido amplamente utilizada com a TRS em pesquisas nacionais na área da Enfermagem (13,14) , bem como, tem atuado como um importante apoio a estudos nacionais (15) e internacionais (16,17) em psicologia, ajudando a entender o assunto como um constituído por interações sociais com outros sujeitos.…”
Section: Métodosunclassified